BS EN IEC 60704-2-14 AMD 2. Household and similar electrical appliances. Test code for the determination of airborne acoustical noise. Part 2-14. Particular requirements for refrigerators, frozen-food storage cabinets and food freezers (19th April 2023) - British Standards Institution,
No abstract available